Emerging models for global health in radiation oncology - Ngwa, Wilfred; Ngoma, Twalib (IOP (Series). Release 2., 2016)
In response to the growing global health challenge in the fight against cancer, there is now a greater need for radiation oncology health professionals across institutions to collaborate and be more globally engaged. Emerging Models for Global Health in Radiation Oncology is a response to the need for a book that comprehensively covers the important and emerging field of radiation oncology. This insightful book highlights the emerging models for global radiation oncology, and serves as a useful resource to facilitate participation and greater effective collaborative global cancer care, research, and education. It is suitable for researchers, students, health professionals, and anyone interested in the global oncology community.